RECOMBINANT CYTOKINES IN THE TREATMENT OF PNEUMONIA. CLINICAL EXPERIENCE - Gizinger, O.A.; Egorova , V. N; Trofimov , V. I. (Interdisciplinary Approaches to Medicine, 2021)
Antimicrobial chemotherapy is a keystone of the treatment of pneumonia. Prescription of antibacterial drugs does not always ensure the success of treatment due to the secondary immune deficiency developing in the process of the disease and the rapid growthof acquired antibiotic resistance. The article presents experience and clinical and immunological effectiveness of the use of recombinant interleukin-2 (rIL-2) in the treatment and prevention of pneumonia in order to reduce the risk of pneumonia in cerebral strokes and severe exogenous poisoning.In our study, we analyzed two clinical cases with of pneumonia. In patients with severe forms of pneumonia using complex therapy with recombinant interleukin-2, the time to achieve clinical and laboratory remission is reduced, the manifestations of respiratory failure and intoxication syndrome are stopped.Thus, аccumulated clinical experience the administration of the recombinant drug interleukin-2 in combination with antimicrobial drugs in basic therapy showed positive effectiveness, validity and expediency, in order to improve the clinical course, normalize immunological parameters, as well as for the rapid and complete treatment of the inflammatory process in patients of different ages with severe pneumonia.